The end of your life book club - Schwalbe, Will. (New York : Alfred A. Knopf, 2012)
The inspiring story of a son and his dying mother, who form a "book club" that brings them together as her life comes to a close.
Crossing to safety -- Appointment in Samarra -- Seventy verses on emptiness -- Marjorie Morningstar -- The hobbit -- Daily strength for daily needs -- People of the book -- "I am sorrow" -- The uncommon reader -- The lizard cage -- Brat Farrar -- Continental drift -- The painted veil -- Murder in the cathedral -- Wherever you go, there you are -- Kokoro -- The price of salt -- The reluctant fundamentalist -- The year of magical thinking -- Olive Kitteridge -- Girls like us -- Suite franȧise -- The bite of the mango -- The elegance of the hedgehog -- The girl with the dragon tattoo -- Brooklyn -- My father's tears -- Too much happiness.
"This is a Borzoi book"--T.p. verso.
Keywords: Schwalbe, Mary Anne; Schwalbe, Will -- Family; Cancer -- Patients -- United States -- Biography; Cancer -- Patients -- Family relationships -- United States; Families -- Books and reading